The Psychological Expectation of New Project Income Under the Influence of the Entrepreneur’s Sentiment From the Perspective of Information Asymmetry - Zhong, Huaqian; Yan, Runyu; Li, Shuai; Chen, Min (Frontiers in Psychology, 2020)
The phenomenon of high first-day income and high break-up rate in China’s capital market has long attracted the attention of investors. Based on the disagreement model, in combination with the information asymmetry theory and behavioral finance, a mathematical model was put forward to analyze the reasons and mechanisms for the excess return of the initial public offering (IPO) on the first-day under the influence of investors’ sentiments. The analysis shows that the IPO first-day income is a function of the disagreement between investors, which generally presents an asymmetric U shape. Information asymmetry affects the degree of valuation deviation. The sentiment of investors reflects the psychological state of the investor at the time, which makes the income increase or decrease under the influence of investor sentiment and market sentiment. In turn, it leads to the emergence of excess returns or break-up rates on the first-day. The research results help deepen the understanding of the IPO pricing mechanism and explore the impact of investor psychology on its pricing, putting forward suggestions for the issue pricing mechanism of the Sci-Tech Innovation Board.